From Teaching to Training: Work Adjustment of Teachers-Turn-Teacher Trainers in A Malaysian Teacher Training Institute - Rouzil Armiza Binti Samsir; Kalsom Binti Ali; Sofia Hayati Yusoff; Abdul Rahim Zumrah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Day by day, more and more teachers are recruited as teacher trainers. Changing work role from a teacher to a trainer requires them to adapt to new work responsibility and tasks. In this study, they are known as teachers-turn-trainers (TTTs). These newcomers need personal and work adjustment during the transition years. This article explores the relationship between the individual-related factors, job-related factors and organizational-related factors; and work adjustment of the TTTs. Self-administered questionnaires which contains 62 items were collected from the respondents and analysed.The need to study stems from the fact that the IPGs are experiencing changes in terms of vision and mission. Based on the Theory of Work Adjustment (TWA), this article reports the findings of the study. Results show that there is a significant relationship between work adjustment and two of the variables selected: Attitudes (.419) and Proactive Personality (.502). Based on Guilford’s rule of thumb, there is a positive and moderate relationship between both the independent variables and work adjustment. In the fast and competitive world, Malaysia is an aggressively developing country. The vision, mission and goals of the Malaysian Education system, need to be supported by many studies. While the body of research seems to be growing on work adjustment abroad, both qualitatively and quantitatively, the number of studies regarding work adjustment in Malaysia is still insufficient.